Unusual caudal cervical fracture in a dog. Issue 1 (5th November 2021) - Jacqmin, Maxime Jean; Baldinger, Arnaud; Combet‐Curt, Julie; Nectoux, Alexandra; Moissonnier, Pierre
Abstract: A 14‐month‐old entire male Saint Bernard dog was presented at the emergency department for paralysis after a head trauma. Computed tomography examination revealed an atypical fracture of C6 with a large free bone fragment in the dorsolateral part of the vertebral canal, originating from the vertebral body. A C6–C7 Funkquist B dorsal laminectomy was performed to remove this intracanalar fragment. A dorsal stabilization using lag screws inserted into the articular facets of C5–C6 and C6–C7 was also performed. The surgical procedure maintained vertebral column stability and allowed a complete functional recovery. The present article exposes the diagnosis and therapeutic management of an original cervical fracture, discusses the choice of a stabilization technique for the caudal cervical spine and the possible underlying predisposing factors that could have led to this unusual fracture.